AB1085 Measuring patient satisfaction of biological treatments in a regional hospital. (15th June 2017) - Grados, D; Retamero, A; Riveros, A; Baliu, C; Nogues, E; Ferrandez, D; Bové, F; Colquechambi, AM; Cucurell, M
Abstract : Objectives: To determine/measure the satisfaction degree of patients with rheumatologic (rheumatoid arthritis, spondyloarthropathies and other arthritis) and dermatological (psoriasis, psoriatic arthritis and suppurative hidrosadenitis) disease treated with a biological drug. Methods: Descriptive prospective study conducted in a Regional Hospital with a reference area of 109, 530 inhabitants. A survey was conducted to all patients, thepatientswhocollectedtheir medication at the Pharmacy Service (self-administration treatment) and the patients who came for consultation (treatment administered by the nursing staff). The satisfaction degree before and after the biological treatmentwas evaluated.From 0 to 10, where 0 was the maximum dissatisfaction and 10 the maximum satisfaction; and improvement of pain, where 0 implied no improvement and 10 maximum improvement. Clinical records were reviewed and a database was generated for exploitation with SPSS-vs 22. All patients received an information sheet from the study and signed an informed consent form. Results: A total of 100 patients were analyzed: 45 men and 55 women. The mean age was 53 years (SD 14.9). 42% of patients were actively employed. Distribution of patients by pathologies: 46 (46%) rheumatoid arthritis, 25 (25%) psoriasis, 16 (16%) psoriatic arthritis, 8 (8%) spondyloarthropathies, 2 (2%) suppurative hydrosadenitis and 1 (1%) juvenile idiopathic arthritis. Distribution of biological drugs: 49 (49%) adalimumab, 20 (20%) ustekinumab, 18 (18%) etanercept, 6 (6%) golimumab, 3 (3%) tocilizumab, 2 (2%) secukinumab, 1 (1%) certolizumab. The treatment was self-administered in 61 patients. Only 30 (30%) patients had undergone previous biological treatment. At present, 43 patients had some additional treatment, 38 with methotrexate and 5 with leflunomide. Conclusions: The satisfaction degree of patients with their biological treatment is very high regardless of the route of administration. Most of them are in monotherapy or with low doses of FAME. 61% of patients self-administer the drug at home. 93% of patients consider that there has been a change in their quality of life and that they can lead a normal life. Disclosure of Interest: None declared